Activation of spinal ephrin‐B3/EphBs signaling induces hyperalgesia through a PLP‐mediated mechanism. (28th December 2021) - Zhang, Pei; Qiao, Zhen; Pan, Shu; Yang, Ping; Zha, Zhengxia; Sun, Suya; Xu, Qiongming; Liu, Xingjun; Xu, Nanjie; Liu, Yanli
Abstract: Ephrin B/EphB signaling pathway is involved in the regulation of pain caused by spinal cord injury. However, the role of ephrin‐B3/EphBs signaling in regulation of nociceptive information is poorly understood. In the present study, formalin‐induced inflammatory pain, mechanical allodynia and thermal hyperalgesia, was measured using Efnb3 mutant mice ( Efnb3 −/− ) and wild‐type ( Efnb3 +/+ ) mice. The spinal cord (L4–6) was selected for molecular and cellular identification by western blotting and immunofluorescence. Efnb3 mutant mice showed a significant increased the thermal and mechanical threshold, followed by aberrant thin myelin sheath. Furthermore, expression of proteolipid protein (PLP) was significantly lower in L4–6 spinal cord of Efnb3 −/− mice. These morphological and behavioral abnormalities in mutant mice were rescued by conditional knock‐in of wild‐type ephrin‐B3. Intrathecal administration of specific PLP siRNA significantly increased the thermal and mechanical threshold hyperalgesia in wild‐type mice. However, overexpressing PLP protein by AAV9‐PLP could decrease the sensitivity of mice to thermal and mechanical stimuli in Efnb3 −/− mice, compared with scrabble Efnb3 −/− mice. Further, Efnb3 lacz mice, which have activities to initiate forward signaling, but transduce reverse signals by ephrin‐B3, shows normal acute pain behavior, compared with wild type mice. These findings indicate that a key molecule Efnb3 act as a prominent contributor to hyperalgesia and essential roles of ephrin‐B3/EphBs in nociception through a myelin‐mediated mechanism.